Study of Non-woven Jute Agrotextile Mulches on Soil Water, Temperature and Nutrient Status in Root Zone in Broccoli (Brassica oleracea L.) Cultivation - Manna, Koushik; Saha, Biplab; Kundu, Manik Chandra (International Journal of Bio-resource and Stress Management, 2022)
The field studies were conducted during the middle of November to end of February for the season of 2015–2016 and 2016–2017 respectively in the red lateritic soil of Bahadurpur village of Bolpur, Birbhum, West Bengal, India which lies between 23°39'47.69'' N latitude and 87°37'36.91'' E longitude with an average altitude of 58.9 m above the mean sea level under sub-humid semiarid region of West Bengal, Eastern India to evaluate the performance of different types of non-woven jute agro-textile mulches (NJATM) in comparison to other mulches on soil temperature, soil moisture, soil physical properties and yield of broccoli (Brassica oleracea L.). The highest pooled yield (8.50 t ha-1) of broccoli was recorded in 350 gsm NJATM treatment. Minimum temperature fluctuation (1−3oC) was observed in case non-woven jute agro textile mulches and it was lowest in 350 gsm NJATM treatment followed by 400 gsm NJATM. In case of soil physical properties, the maximum mean value of hydraulic conductivity (0.54 cm hr-1) was observed in 400 gsm NJATM. However, the lowest pooled Bulk Density was recorded in 400 gsm NJATM treatment (1.37 g cm-3) which was, however, statistically at par with 350 gsm NJATM treatment (1.38 g cm-3).The soil moisture was conserved in all treatments compared to control showing highest moisture content in 400 gsm NJATM treatment. Organic carbon content of soil was increased in all mulch treated plots compared to control, and their initial value and their highest value (0.64%) was recorded in 350 gsm NJATM treatment The NJATM of 350 gsm thickness was very effective compared to other mulches as a result of the soil management practices and productivity.